2010
DOI: 10.1074/jbc.m110.171793
|View full text |Cite
|
Sign up to set email alerts
|

Pentameric Organization of the Ribosomal Stalk Accelerates Recruitment of Ricin A Chain to the Ribosome for Depurination

Abstract: Ribosome inactivating proteins (RIPs) depurinate a universally conserved adenine in the ␣-sarcin/ricin loop (SRL) and inhibit protein synthesis at the translation elongation step. We previously showed that ribosomal stalk is required for depurination of the SRL by ricin toxin A chain (RTA). The interaction between RTA and ribosomes was characterized by a twostep binding model, where the stalk structure could be considered as an important interacting element. Here, using purified yeast ribosomal stalk complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 48 publications
6
55
0
Order By: Relevance
“…To compare the interaction of Stx1A1 and Stx2A1 with the ribosome, the untagged A1 subunits were immobilized on a CM5 chip of the Biacore T200 instrument at 1,692 RU and 1,672 RU, respectively, using amine coupling, and their interaction with yeast ribosomes was measured by single-cycle kinetic analysis by passing ribosomes over the surface at different concentrations. Since the surface is not regenerated between injections in the single-cycle analysis, multiple samples can be analyzed in a shorter period of time, allowing comparison of levels of binding under identical conditions (38). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To compare the interaction of Stx1A1 and Stx2A1 with the ribosome, the untagged A1 subunits were immobilized on a CM5 chip of the Biacore T200 instrument at 1,692 RU and 1,672 RU, respectively, using amine coupling, and their interaction with yeast ribosomes was measured by single-cycle kinetic analysis by passing ribosomes over the surface at different concentrations. Since the surface is not regenerated between injections in the single-cycle analysis, multiple samples can be analyzed in a shorter period of time, allowing comparison of levels of binding under identical conditions (38). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the interaction of Stx1 and Stx2 with either the ribosome or the ribosomal stalk complex has not been investigated. To investigate the basis for the higher activity of Stx2A1, we compared the interactions of the A1 subunits with yeast ribosomes and with the isolated ribosomal P-protein stalk pentamer from yeast (38). Our previously reported results indicated that the interaction of RTA with ribosomes did not fit a simple 1:1 interaction model (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most prominent feature of the eukaryotic stalk proteins is the highly conserved motif present in the C-terminal part of the uL10 and P1/P2 proteins, consisting of a stretch of highly acidic and hydrophobic amino acids involved in interaction with translational GTPases (trGTPases) and RIPs (21). We established that the ribosomal stalk is the primary docking site for the ricin A chain (RTA) on the ribosome (13) and showed that multiplication of P-proteins is a critical factor accelerating the recruitment of RTA to the ribosome (22). Using the yeast model, we showed that the two P1A/P2B and P1B/P2A stalk dimers on the ribosome do not contribute equally to the interaction of ribosomes with RTA (23).…”
mentioning
confidence: 99%